KARAKTERISTIK KIMIA ROTI PREBIOTIK DARI BERBAGAI PATI SAGU HASIL MODIFIKASI - Abdul Rahim; Gatot Siswo Hutomo; Made Tangkas; Rosmianti; Putri Andini; Andri; Chitra Anggriani Salingkat (Fakultas Pertanian Universitas Alkhairaat Palu, 2022)
The purpose of this research is the chemical characteristics of prebiotic bread from various modified sago starch, namely acetylated sago starch (ASS), butyrylated sago starch (BSS), phosphorylated sago starch (PSS). Preparation of prebiotic bread was done by using a ratio of wheat flour (WF) with a single modified sago starch consisting of 360 WF:0; 180 WF: 180 ASS; 180 WF: 180 BSS and 180 WF: 180 PSS with 4 replicates. Research parameters include water, ash, fat, protein, fiber and carbohydrate content. The results showed that the best prebiotic bread was obtained at 180 WF:180 ASS with 28.33% water, 0.79% ash, 3.58% fat, 6.85% protein, 0.096% fiber and 58.98% carbohydrates. Modified sago starch has been potential as an alternative raw material for the manufacture of prebiotic bread.